Pregnant Women Develop a Specific Immunological Long-Lived Memory Against SARS-COV-2 - Fenizia, Claudio; Cetin, Irene; Mileto, Davide; Vanetti, Claudia; Saulle, Irma; Di Giminiani, Maria; Saresella, Marina; Parisi, Francesca; Trabattoni, Daria; Clerici, Mario; Biasin, Mara; Savasi, Valeria (Frontiers in immunology, 2022)
It is well established that pregnancy induces deep changes in the immune system. This is part of the physiological adaptation of the female organism to the pregnancy and the immunological tolerance toward the fetus. Indeed, over the three trimesters, the suppressive T regulatory lymphocytes are progressively more represented, while the expression of co-stimulatory molecules decreases overtime. Such adaptations relate to an increased risk of infections and progression to severe disease in pregnant women, potentially resulting in an altered generation of long-lived specific immunological memory of infection contracted during pregnancy. How potent is the immune response against SARS-CoV-2 in infected pregnant women and how long the specific SARS-CoV-2 immunity might last need to be urgently addressed, especially considering the current vaccinal campaign. To address these questions, we analyzed the long-term immunological response upon SARS-CoV-2 infection in pregnant women from delivery to a six-months follow-up. In particular, we investigated the specific antibody production, T cell memory subsets, and inflammation profile. Results show that 80% developed an anti-SARS-CoV-2-specific IgG response, comparable with the general population. While IgG were present only in 50% of the asymptomatic subjects, the antibody production was elicited by infection in all the mild-to-critical patients. The specific T-cell memory subsets rebalanced over-time, and the pro-inflammatory profile triggered by specific SARS-CoV-2 stimulation faded away. These results shed light on SARS-CoV-2-specific immunity in pregnant women; understanding the immunological dynamics of the immune system in response to SARS-CoV-2 is essential for defining proper obstetric management of pregnant women and fine tune gender-specific vaccinal plans.